Electrochemical modification and analytical exploration of resazurin as a redox-active probe for electrochemical biosensors - Balamurugan Thangavel; Won Han; Joong Ho Shin (Electrochemistry Communications)
An electrochemical potential-assisted functionalization strategy is used to immobilize resazurin (AZ) on multiwalled carbon nanotube surfaces in a physiological buffer leading to the formation of a resorufin/dihydro resorufin (RR/DRR) redox couple. The electrochemical characterizations that reveal the modified surface are surface-confined behavior with an electron transfer rate constant of 4.4 s−1. Thus modified RR/DRR redox couple was found to modulate the interfacial characteristics to the benefits of bio-electrocatalysis since the redox molecule has sensitivity to pH, negative redox potential, and selectivity to analytes. The hydrogen peroxide (H2O2) reduction and sensing performance of the AZ-modified electrode surface were evaluated. The experimental results revealed the direct detection of high concentrations of H2O2 at the electrified interface before the oxygen reduction potential. Furthermore, the designed sensor exhibited high selectivity for H2O2 even in the presence of interfering molecules in the solution. In addition, for the demonstration, the glucose oxidase enzymes were immobilized on carbon nanotubes modified with an RR/DRR redox couple, and the electron tunneling behavior was investigated. The developed sensor could be used for the reagent-less electrochemical biosensing of glucose up to 30 mM. Thus, the AZ-based redox electrode catalysts can be applied in diverse biosensor applications.